Optical Anisotropy in van der Waals materials: Impact on Direct Excitation of Plasmons and Photons by Quantum Tunneling - Zhe Wang (Nature Publishing Group, 2021)
Enhancement in local density of optical states arising from the optical anisotropy of hexagonal boron nitride significantly improves the emission rates of plasmons and photons in quantum mechanical tunnel junctions.